Nuevos enfoques en cirugía perirradicular : Revisión de literatura (2000)
ABSTRACT: When aperiapicallesion is generated as a consequence of a chronic inflamatory process and subsequent pulpar necrosis appears, a therapy directed to elimina te the primar y etiologic agent is needed and frecuently heals successfully with a conventional endodontic therapy. However in some cases a infectious condition persists. showing aperiapical pathology Jike a granuloma or periapical cyst, with or without sinous tracts. When the infection can 'tbe removed by an orthograde way,.an endodontic surgery is indicated. Sometiries the periapical bone defects don 'tregenera te beca use the oral epithelium and/orconective tissue migration towards the bone cavity, a voiding the formation of normal trabecular bone and a new surgery is required. The scientific literature reportsnew root-end filling materials and guided tissue regeneration materials to improve the surgery treatmen predictibiJity. At the present time others materials are substituing the conventional amalgam as root-end sealing Iike: new zinc oxide and eugenol derived materials (IRM and Super EBA) and recently the MTA or mineral trioxideaggregate. Theguided tissue regeneration materials are:bioabsorbables and not bioebsorbebles membranes and substitutes materials (hidroxiapatiteand Iiophilized bone)and freeand pedic/ed autogenous periosteal grafts.